A Categorical Equivalence for Tense Nelson Algebras - Figallo, Aldo Victorio (2021)
In this paper we present a category equivalent to that of tense Nelson algebras.The objects in this new category are pairs consisting of an IKt-algebra and a Boolean IKtcongruenceand the morphisms are a special kind of IKt-homomorphisms. This categoricalequivalence permits understanding tense Nelson algebras in terms of the better?knownIKt-algebras.